Synthesis, crystal structures and magnetic properties of tetrakis(12-carboxylate)-bridged dimeric gadolinium(III) complexes - Liang Tong, Ming-; Yuan Zhou, Zhong-; Luan Wu, Yu-’; Ming Chen, Xiao- (Malaysian Journal of Science, 1996)
Four dimeric gadolinium(III) complexes, [Gd2(pybet)4(H20)8](C104)6 (1), [Gc12(pybet)4(phen)4](C104)6.3H20 (3), [Gd2(pybet)6(phen)2(H20)2J(C104)6.2H20 (4), and [Gd2(ppbet)6(bpy)2](C104)6.3H20 (5) (pybet = C51-15N+CH2CO2-, ppbet = C5H5N+CH2CH2CO2, phen = 1,10-phenanthroline, bpy-. 2,2’-bipyridine) have been prepared and structurally characterized by X-ray crystallography. The complexes comprise discrete quadruply carboxylate-0,0’ bridged [Gd2(carboxylate)4]6+ dimeric cores in which each metal atom is further coordinated by four terminal aqua ligands, one monodentate pybet carboxylate group and three aqua ligands, two phen ligands and a bpy ligand and a chelate ppbet carboxylate group for 1, 3, 4 and 5, respectively. In the four complexes, the metal atoms all adopt distorted squareÂantiprismatic coordination geometries. The variable-temperature (4Â300 K) magnetic susceptibility of 5 has been determined and the observed susceptibility data were fitted to the theoretical magnetic equation. The exchange integral J was found to be 0.037 cm-’, indicating very weak ferromagnetic spin-exchange interaction between the pair of Gd(III) ions in the dimers. Four dimeric gadolinium(III) complexes, [Gd2(pybet)4(H20)8](C104)6 (1), [Gc12(pybet)4(phen)4](C104)6.3H20 (3), [Gd2(pybet)6(phen)2(H20)2J(C104)6.2H20 (4), and [Gd2(ppbet)6(bpy)2](C104)6.3H20 (5) (pybet = C51-15N+CH2CO2-, ppbet = C5H5N+CH2CH2CO2, phen = 1,10-phenanthroline, bpy-. 2,2’-bipyridine) have been prepared and structurally characterized by X-ray crystallography. The complexes comprise discrete quadruply carboxylate-0,0’ bridged [Gd2(carboxylate)4]6+ dimeric cores in which each metal atom is further coordinated by four terminal aqua ligands, one monodentate pybet carboxylate group and three aqua ligands, two phen ligands and a bpy ligand and a chelate ppbet carboxylate group for 1, 3, 4 and 5, respectively. In the four complexes, the metal atoms all adopt distorted squareÂantiprismatic coordination geometries. The variable-temperature (4Â300 K) magnetic susceptibility of 5 has been determined and the observed susceptibility data were fitted to the theoretical magnetic equation. The exchange integral J was found to be 0.037 cm-’, indicating very weak ferromagnetic spin-exchange interaction between the pair of Gd(III) ions in the dimers.